How can we value an environmental asset that very few have visited or heard of? Lessons learned from applying contingent and inferred valuation in an Australian wetlands case study. (15th August 2018) - Gregg, Daniel; Wheeler, Sarah Ann
Abstract: To date, the majority of environmental assets studied in the economic valuation literature clearly have high amenity and recreational use values. However there are many cases where small, but nevertheless unique and important, ecosystems survive as islands amongst large areas of modified, productive, or urban, landscapes. Development encroaches on the landscape and as urban landscapes become more concentrated these types of conservation islands will become increasingly more important. Previous experience with economic valuation suggests that lower total values for smaller contributions to conservation are more liable to be swamped by survey and hypothetical bias measures. Hence there needs to be more understanding of approaches to economic valuation for small and isolated environmental assets, in particular regarding controlling stated preference biases. This study applied the recently developed method of Inferred Valuation (IV) to a small private wetland in South-East Australia, and compared willingness to pay values with estimates from a standard Contingent Valuation (CV) approach. We found that hypothetical bias did seem to be slightly lower with the IV method. However, other methods such as the use of log-normal transformations and median measures, significantly mitigate apparent hypothetical biases and are easier to apply and allow use of the well-tested CV method. Highlights: Inferred valuation generated smaller willingness to pay differences than contingent valuation estimates. Simple, outlier-robust, methods produced greater reductions in estimated mean willingness to pay. Significant public value was estimated for conserving privately held, small but high biodiversity environmental assets.